2022
DOI: 10.3390/polym15010075
|View full text |Cite
|
Sign up to set email alerts
|

Crystallinity Dependence of PLLA Hydrophilic Modification during Alkali Hydrolysis

Abstract: Poly(L-lactic acid) (PLLA) has been extensively used in tissue engineering, in which its surface hydrophilicity plays an important role. In this work, an efficient and green strategy has been developed to tailor surface hydrophilicity via alkali hydrolysis. On one hand, the ester bond in PLLA has been cleaved and generates carboxyl and hydroxyl groups, both of which are beneficial to the improvement of hydrophilicity. On the other hand, the degradation of PLLA increases the roughness on the film surface. The r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…The polymeric chains of PLA, PLGA, and PS are mostly hydrophobic. At high pH, the PLA or PLGA molecules undergo hydrolysis 44,45 and are broken down into smaller molecules. Hydrolysis generates carboxylic acid groups as the terminated groups of the smaller PLA or PLGA molecules.…”
Section: Pla (75 Wt%) Was Dissolved In Chloroform For Forming Thementioning
confidence: 99%
“…The polymeric chains of PLA, PLGA, and PS are mostly hydrophobic. At high pH, the PLA or PLGA molecules undergo hydrolysis 44,45 and are broken down into smaller molecules. Hydrolysis generates carboxylic acid groups as the terminated groups of the smaller PLA or PLGA molecules.…”
Section: Pla (75 Wt%) Was Dissolved In Chloroform For Forming Thementioning
confidence: 99%
“…59,[61][62][63][64][65][66] Studies have shown that the hydrophobicity and acidic products of PLLA might affect cell adhesion. 143,157 Nevertheless, when used as the fabric component for Absnow and modified Amplazter occluders, it demonstrated a satisfactory endothelialization process and tolerable inflammatory response, proving its feasibility as a fabric material. [61][62][63][64]68,69,71,72 Various methods, such as surface treatment, chemical crosslinking, and blending with other materials can modify the mechanical properties, hydrophobicity, and degradation time of PLLA, making it one of the most promising candidates materials for both skeleton and fabric of bioabsorbable cardiac occluders.…”
Section: Poly-ε-caprolactonementioning
confidence: 99%
“…To keep the mechanical strength of the occluder for its functioning, additional locking systems are required when PLLA is used as the skeleton material in both PLLA/PDLLA and Absnow occluders 59,61–66 . Studies have shown that the hydrophobicity and acidic products of PLLA might affect cell adhesion 143,157 . Nevertheless, when used as the fabric component for Absnow and modified Amplazter occluders, it demonstrated a satisfactory endothelialization process and tolerable inflammatory response, proving its feasibility as a fabric material 61–64,68,69,71,72 .…”
Section: Application Of Biodegradable Polymers In Absorbable Cardiac ...mentioning
confidence: 99%
“…There are many methods for surface modification of hydrophobic PLA, PCL, and PLCL. The most common are plasma etching, physical coating, and hydrolysis to physically and chemically immobilize biological substances, such as proteins and polysaccharides (29) .…”
Section: Mineralization Of Cellsmentioning
confidence: 99%